Di-vizije družbenega sveta in potencialnost delovanja v intersubjektivnosti - Perger, Nina (Družboslovne razprave, 2017)
In this article, we analyse theoretical works of P. Bourdieu and J. Butler regarding how they approach the intersection of objective structures and social actors. While Bourdieu emphasises social reproduction with the concepts of habitus and undetermined embodiment of objective structures, J. Butler focuses on subversions through the concepts of performativity and non-identical and, as such, always "unsuccessful" reiterations of social norms. Moreover, they both primarily focus on the individual level, neglecting the level of intersubjectivity that in Bourdieu's work is mostly considered through the principle of homology, while J. Butler, along with certain other authors, acknowledges intersubjectivity in terms of its potential "supporting" infrastructure and alternative schemes of marginalised, alternative di-visions of the social world.
Keywords: Družbena moč; Social power; Intersubjectivity; Intersubjektivnost; družbene strukture